2020
DOI: 10.1021/acs.langmuir.0c00576
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization-Driven Flows within Evaporating Aqueous Saline Droplets

Abstract: Using micro-PIV (Particle Image Velocimetry), we observe for the first time, the direct correlation between crystallisation and hydrodynamics in evaporating micro-litre saline (1M NaCl) sessile drops. The relationship is demonstrated by a remarkable jet of liquid along the base of the drops, induced by and directed at the point of nucleation and subsequent crystal growth. Prior to 2 nucleation the flow is more uniformly outward with the magnitude of the velocity decreasing with time. From calculations and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…The wetting property of the glass surface and the emerging crystals, and crystallization-driven flow of solutes may control the subsequent patterns after initial nucleation. 35,36 A relatively higher evaporation rate seems responsible for the patterns observed on the center (Figure 1d), creating tiny outward radiating crystals.…”
Section: ■ Resultsmentioning
confidence: 92%
“…The wetting property of the glass surface and the emerging crystals, and crystallization-driven flow of solutes may control the subsequent patterns after initial nucleation. 35,36 A relatively higher evaporation rate seems responsible for the patterns observed on the center (Figure 1d), creating tiny outward radiating crystals.…”
Section: ■ Resultsmentioning
confidence: 92%
“…Generally, crystallization or nucleation starts near the triple-phase contact line because evaporation and consequently solute concentration are maximum therein. This problem has been studied on a droplet . The thin-film evaporation and drying process can be similar since both undergo either a high rate of evaporation or a concentration gradient at the triple-phase line with the same triple-phase profile.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we studied different stages of evaporation and explained a possible analogy between the droplet and thin liquid film. To explore potential relation, we used some cues from the Ristenpart et al and Ajaev et al saline droplet studies to investigate the deposition pattern. Furthermore, wettability, solution concentration, and the substrate pattern for a variety of droplet sizes have shown an imperative impact on the deposition and internal flow patterns.…”
Section: Introductionmentioning
confidence: 99%
“…They found the formation of volcano-like structures at the center of the deposit. Very recently, Efstratiou et al [ 50 ] found the formation of a rim of evenly spaced salt crystals instead of a continuous rim after the evaporation of aqueous saline droplets. Furthermore, they also found that the type of salt, its initial concentration, and the hydrophilic or hydrophobic character of the substrate can drive the formation of salt deposits with very different morphologies, e.g., continuous rings, concentric rings, or discrete crystals, close to the ring or at the center of the deposit.…”
Section: Resultsmentioning
confidence: 99%